Processing procedures and feeding systems for sorghum-based diets given to lactating sows - Kim, I.H.; Hancock, Joe D.; Burnham, L.L.; Kennedy, G.A.; Nichols, David A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One-hundred twenty nine primiparous sows were used to determine the effects of alternative processing procedures and feeding systems on the nutritional value of sorghum grain-based diets for lactating sows. Treatments were a ground sorghum control, steam- flaked sorghum and extruded sorghum fed in meal form, or the ground sorghum control given as pellets or gruel (1: 1 ratio of water and feed on a volume:volume basis). Average daily feed intake was greater for sows fed pelleted and gruel forms compared to sow fed the diets with steam-flaked and extruded sorghum. However, no differences occurred in sow weight or backfat losses among the treatments. Number of pigs weaned and percentage survivability were similar among treatments, except that steam-flaked sorghum supported greater litter weight gains than extruded sorghum. Apparent digestibilities of OM, N, and GE in sows fed steam-flaked and extruded sorghum were greater than in sows fed pelleted or gruel diets. Sows fed extruded sorghum tended to have the greatest digestibilities of OM, N, and GE and lowest excretions of DM and N in the feces. Severity of ulceration was not affected significantly by treatments, but keratinization was greatest for sows fed extruded sorghum. In conclusion, the alternative processing methods (steam-flaking and extrusion) and feeding systems (pellets and gruel) had little effect on sow and liner performance. However, nutrient digestibilities were improved for all treatments that involved heating (steam flaking, extrusion, and pelleting), and, thus, these treatments resulted in less fecal excretion of DM and N.
Keywords: Swine; Sow; Sorghum; Steam-flake; Extrusion; Pellet; Gruel; Digestibility